Komunikasi Kebijakan Perlindungan Anak di Ruang Digital: Studi Komparatif antara PP Tunas dan Regulasi Global - Novida Irawan; Marwan Albab; Radyta A. Burhanuddin; Salsabila Nurazhara; Cezha Asti Ananta; Rafi Fikri Mahendra; Sahnela Innayah (Jurnal Sosial Humaniora dan Pendidikan, 2026)
The massive development of digital technology expands children's access to information while simultaneously escalating cyber risks such as online exploitation and cyberbullying. This study aims to analyze the implementation of Government Regulation Number 17 of 2025 concerning Electronic System Governance for Child Protection (PP TUNAS) in the digital space, focusing on the technical challenges of age verification and the strengthening of digital literacy. This research employs a descriptive qualitative approach using qualitative content analysis of relevant regulatory documents, methodologically triangulated with secondary questionnaire data from the EVIDENT Institute involving 1,050 urban respondents in DKI Jakarta. The analytical framework is examined through Edwards III's Policy Implementation Theory, which measures four main variables—communication, resources, disposition, and bureaucratic structure—supported by Ayres and Braithwaite's Responsive Regulation Theory. The findings indicate a wide operational gap between normative regulatory texts and the reality of digital platform architecture. First, in the technical resource dimension, the age verification mechanisms of most platforms still rely on vulnerable self-declaration methods, deemed ineffective by 59.3% of respondents. Second, in the communication dimension, a substantial information asymmetry emerges, with 45% of respondents in a state of pseudo-awareness. Third, there is an imbalance between the domestic parental supervision burden and the fragmentation of the educational bureaucracy, reflected in 31.8% of educational institutions that have not facilitated digital literacy socialization for the parent community. This study concludes that strengthening PP TUNAS implementation requires integrating verification systems based on national population data (NIK) and standardizing a national digital citizenship curriculum to close the digital loophole.